Perceived Attractiveness of Structured Financial Products: The Role of Presentation Format and Reference Instruments. Issue 1 (2nd January 2020) - Anic, Vladimir; Wallmeier, Martin
Abstract: Structured equity-linked products hold a strong position in the asset universe in Europe, although they are often considered to be overly complex. Their risk and return profile is typically presented by simple payoff diagrams and verbal descriptions. The authors propose to complement the payoff diagrams with information on the payoff's probability distribution and study different presentation formats in an experimental setting with multiple investment decisions. They introduce a flexible framework for designing tailor-made products, which allows them to implement a part of the experiment as an interactive exploration in which the participants experience the risk-return tradeoff and the role of different features of structured products. The authors find that displaying probability histograms can have a strong effect on the perceived attractiveness of the products by revealing the loss probability. In contrast to common practice, the present results suggest that the reference instrument shown in graphical displays should be risk-adjusted to match the risk of the structured product. Otherwise, a preference for lower risk might be misinterpreted as a preference for a specific return profile. These findings can be used to improve information documents for investors such as the "Key Information Document" required by European regulation.